Investigating Urban Inequalities in a Climate Crisis Scenario: the Contribution of Big Data to Environmental Justice Studies - Landi, Alessandra; Rimondi, Tommaso (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
This paper moves from the idea that cities represent a central “battlefield” for today’s environmental challenges. Climate change, in particular, poses significative threats for urban landscapes and communities living in urban space. On the one hand, today’s challenges have significant continuities with classical urban issues: cities have always been space of conflicts, contradictions, inequalities. Environmental issues represent one of the many stressors of urban dynamics; conflicts on the locations of polluting sites, for example, have developed over the last fifty years, intertwined with segregation and discrimination processes. On the other hand, the central role of the environment in current policies, framed as “sustainability policies”, need a specific, renewed and stronger focus on urban inequalities, that can significantly benefit from new analytical tools, such as Big data. The first paragraph give a short perspective on environmental justice history and main topics, focusing in particular on its lasting interest for spatial inequalities and discrimination processes. The second paragraph underlines how, within the context of climate change, such perspective proves to be still useful, permitting to deepen our understandings of vulnerabilities and recovery processes in the aftermath of disasters, or resilience planning’s failures. The third and last paragraph illustrates how new analytical tools, such as Big Data or ecometrics, can be used to inform local policies and strengthen cooperation between activists, citizen, administrators and academics in tackling inequalities within the urban fabric.